Effectiveness of Peat Coagulant for the Removal of Textile Dyes from Aqueous Solution and Textile Wastewater - Uddin, A.B.M. Helal Uddin; Sujari, Amat Ngilmi Ahmad; Nawi, Mohd. Asri Mohd. Nawi (Institut Kimia Malaysia, 2003)
Tropical peat soil after chemical modifica tion was found to be an effective coagulant for clarification of some textile dyes from their aqueous solution. A thorough comparative study with conve ntional coagulant had also been done. Results show that it can remove reactive, vat and disperse dyes from their 50 mgIL aqueous solution. It was found that the removal for reactive blue 19 and cibacron brilliant red was 99% and 97%, vat blue 14 and disperse red 72, 98% and 97% respectively. Even though our study with 10% alum and PAC (Poly Aluminium Chloride) solution showed a 100% removal of disperse and vat dyes, both of them showed a poor removal of two reactive dyes. Peat coagulant had a wide pH working range, however its optimum pH range was from pH 3 to 5. On the other hand, alum and PAC showed specific working pH of 5 for two reactive dyes, but they showed wide pH working range for disperse and vat dyes. The mechanism for coagulation by peat coagulant was proven as charge adsorption neutralisation process. The study with textile wastewater shows a 94% removal of colour and 98% removal of suspended solids by using peat coagulant.